BEYOND THE CLASSROOM: FACTORS SHAPING TEACHER EFFECTIVENESS IN UPPER PRIMARY SCHOOLS - Christopher, T Arun; C, Brintha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Effective teaching has continuously been under focus in spite of technological advancements and modern resources available in the school. Effective teaching is critical for student success in the 21st century. This study investigates the factors influencing teacher effectiveness in upper primary schools in Kanchipuram district, Tamil Nadu, India. The research examined the impact of school location, management type, and teacher age on instructional delivery. A sample of 700 upper primary teachers participated in the study. Data were analyzed using one-way ANOVA and independent t-tests. The findings revealed that while school location had a negligible impact, school management type, teacher age, and experience significantly influenced teacher effectiveness. Post-hoc analysis using Tukey's HSD test further clarified the direction of these significant differences. The study emphasizes the importance of effective teacher training, professional development, and supportive school environments to enhance the quality of education and prepare students for future challenges.